Before I fall - Oliver, Lauren, 1982- (New York : Harper, 2011)
After she dies in a car crash, teenage Samantha relives the day of her death over and over again until, on the seventh day, she finally discovers a way to save herself.
Wilson's Senior High School, February 2011
School Library Journal, April 2010
Library Media Connection starred, January 2010
Pub Weekly, January 2010
Booklist, October 2009
Horn Book, October 2010
Keywords: Dead -- Juvenile fiction; Interpersonal relations -- Juvenile fiction; Popularity -- Juvenile fiction; Self-perception -- Juvenile fiction; Conduct of life -- Juvenile fiction; High schools -- Juvenile fiction; Schools -- Juvenile fiction; Dead -- Fiction; Interpersonal relations -- Fiction; Popularity -- Fiction; Self-perception -- Fiction; Conduct of life -- Fiction; High schools -- Fiction; Schools -- Fiction; Death -- Fiction; Interpersonal relations -- Fiction; Popularity -- Fiction; Self-perception -- Fiction; Conduct of life -- Fiction; High schools -- Fiction; School stories